Romance and Sexual Initiation among Unmarried Young People in Vietnam: A Multi-Method Approach - TEERAWICHITCHAINAN, Bussarawan (Institutional Knowledge at Singapore Management University, 2007)
Young men represent the highest proportion of sexually experienced unmarried population in Vietnam. Increasing levels of sexual activity, combined with reported low levels of knowledge about sex, HIV/AIDS, and STIs and an aversion to using contraceptives, suggest that they are ill-prepared to deal with Vietnam's emerging HIV epidemic. This study uses a multi-method approach to assess sexual activity and attitudes concerning romantic love among never-married men. I analyze the nationally representative Survey Assessment of Vietnamese Youth to examine patterns of emotional relationships and physical behaviors preceding young men's sexual initiation as well as determinants of premarital sex and an aversion to contraceptive use. Additionally, I analyze data from in-depth interviews to address social contexts in which sexual activities of male adolescents take place. Vietnam’s economic liberalization, which enhanced personal freedom and lessened parental control over children, combined with its cultural predisposition towards romantic love may explain the recent rising trends in sexual activities among young Vietnamese.